2008
DOI: 10.1021/ja0762588
|View full text |Cite
|
Sign up to set email alerts
|

Metal−Peptide Frameworks (MPFs):  “Bioinspired” Metal Organic Frameworks

Abstract: Chiral metal-organic frameworks (MOFs) have attracted a growing interest for their potential use in energy technologies, asymmetric catalysis, chiral separation, and on a more basic level, the creation of new topologies in inorganic materials. The current paper is the first report on a peptide-based MOF, a metal peptide framework (MPF), constructed from an oligovaline peptide family developed earlier by our group (Mantion, A.; et al. Macromol. Biosci. 2007, 7, 208). We have used a simple oligopeptide, Z-(L-Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 62 publications
0
116
0
Order By: Relevance
“…In 2008, Taubert and Mantion et al reported the fi rst example of metal peptide frameworks (MPFs) 28, also termed "bioinspired" analogues to the wellknown MOFs, assembled from an oligovaline peptide Z-(LVal) 2 -L-Glu(OH)-OH through metal-oxygen and metal-nitrogen bonding and various types of hydrogen bonding along with π … π stacking ( Figure 12 ). [ 80 ] The structure of MPF 28 can be described in terms of two 2D substructures interconnected via hydrogen bonding, i.e. the fi rst is a double layer of copper ions in the ab plane that are diagonally displaced with respect to one another, and the second double layer in the ab plane is that of the peptide with its long molecule axis oriented roughly along [001].…”
Section: Reviewmentioning
confidence: 99%
“…In 2008, Taubert and Mantion et al reported the fi rst example of metal peptide frameworks (MPFs) 28, also termed "bioinspired" analogues to the wellknown MOFs, assembled from an oligovaline peptide Z-(LVal) 2 -L-Glu(OH)-OH through metal-oxygen and metal-nitrogen bonding and various types of hydrogen bonding along with π … π stacking ( Figure 12 ). [ 80 ] The structure of MPF 28 can be described in terms of two 2D substructures interconnected via hydrogen bonding, i.e. the fi rst is a double layer of copper ions in the ab plane that are diagonally displaced with respect to one another, and the second double layer in the ab plane is that of the peptide with its long molecule axis oriented roughly along [001].…”
Section: Reviewmentioning
confidence: 99%
“…For example, it should be possible to adsorb targeted molecules if specific interactions sites are suitably located on regular micropores. [40] With this principle, MOFs with pores containing fullerenes, [41] peptides [42] or specific chirality [43,44] have been reported and studied. Although a range of functional MOFs have been produced through ligand design, it is also noteworthy that many functional groups cannot survive the severe MOF formation conditions (e.g., pH, temperature) and impede the formation of the reticular frameworks.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Selected IR data (KBr disc, cm −1 ): 3287,3063,2976,2867,2560,1713,1643,1536,1434,1408,1340,1325,1295,1269,1243,1072,1026,1002,919,895,819,738,673,644. (2). The same procedure was followed for the preparation of all compounds, so only the synthesis of 2 is described in detail.…”
Section: Synthetic Partmentioning
confidence: 99%
“…2 In addition, coordination polymers based on amino acid backbones have gained widespread interest due to their intriguing properties such as asymmetric catalysis, chiral sorption, etc.…”
Section: Introductionmentioning
confidence: 99%